Pesticide handling application in paddy field at Sungai Rambai, Merlimau, Malacca / Siti Nur Syafiqah Sabri - Syafiqah Sabri, Siti Nur (Faculty of Plantation and Agrotechnology, 2016)
Effective pesticide handling consist of safe, effective procedures and responsible for pesticide use can help protect the farmer, water supplies and environments. The farmers had poor knowledge about pesticide toxicity and the majority of farmers did not use appropriate Personal Protective Equipment (PPE). The objective of this study are to identify the implementation of PPE on the procedure and to determine the knowledge of farmer on pesticides handling. The questionnaire on handling practices among farmers is conducted at Sg. Rambai, Merlimau, Malacca on 58 respondents. Based on the results, the implementation ofPPE is according to the procedure but the farmers are not fully equipped with PPE. Meanwhile, farmers with experience from 11 until 15 years showed high knowledge on pesticides handling. In conclusion, experience and knowledge affect the awareness and handling of pesticides by the farmers in paddy field. The background of the studies was referred to the gender, age, year of education, educational level, hectare, activities, and experience handling pesticides. Most of the farmers were male and the range of age 51 and above years old. Most of the farmers (44.8%) only have below 15 years' experience in managing paddy field. The results of this study indicate that most farmers in this district need more education program regarding the safety and use of pesticide. Legislation promoting the use of safer pesticides is also needed. This poses a danger of acute intoxication chronic health problems and environmental pollution. Training of farmers in Integrated Pest Management (IPM) methods, use of proper hygiene and Personal Protective Equipment (PPE) when handling pesticides should be done regularly.